6r+7-9r-19=

Simple and best practice solution for 6r+7-9r-19= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6r+7-9r-19= equation:


Simplifying
6r + 7 + -9r + -19 = 0

Reorder the terms:
7 + -19 + 6r + -9r = 0

Combine like terms: 7 + -19 = -12
-12 + 6r + -9r = 0

Combine like terms: 6r + -9r = -3r
-12 + -3r = 0

Solving
-12 + -3r = 0

Solving for variable 'r'.

Move all terms containing r to the left, all other terms to the right.

Add '12' to each side of the equation.
-12 + 12 + -3r = 0 + 12

Combine like terms: -12 + 12 = 0
0 + -3r = 0 + 12
-3r = 0 + 12

Combine like terms: 0 + 12 = 12
-3r = 12

Divide each side by '-3'.
r = -4

Simplifying
r = -4

See similar equations:

| 3/4g=−12 | | -9-4=5x+12 | | 13+4-6n-2n=5-n+5n | | 1.5j=36 | | 110+10.5x=16x | | 9h-2h+18h=14 | | 3x•4-4=1/5(y-5) | | 3(x+-2)+5x=18 | | 110+10.5x=15.25x | | 9/10-1/15 | | 110+10.5x=15.50x | | 6r+7+9r-19= | | 110+10.5x=15.75x | | 9(X+3)=4(x-3) | | 3(8-2)+5x=18 | | -36/9/7(-23/4)= | | 2+3(x-8)+1=5x-2(x+9) | | 4=6r+7-7r | | 110+9x=15.50 | | 2x=34+8x | | 110+9x=14.50 | | 5x-2(x+6)+2=10-x | | 0.3(p-2)=5-0.6 | | 100+10.5x=16.5x | | 100+10.5x=16x | | 5m-3=3m-7 | | 3(x-16)-(x+10)=-22 | | 75+10.5x=15.50x | | -4(3y-8)+3(2y+10)= | | 0.6(x-8)=3.6 | | N×3/5=1 | | 14n+11=5(n+4) |

Equations solver categories